Corporate Governance and Performance around the World : What We Know and What We Don't - Love, Inessa (World Bank, 2013)
The author surveys a vast body of literature devoted to evaluating the relationship between corporate governance and performance as measured by valuation, operating performance, or stock returns. Most of the evidence to date suggests a positive association between corporate governance and various measures of performance. However, this line of research suffers from endogeneity problems that are difficult to resolve. There is no consensus yet on the nature of the endogeneity in governance–performance studies and in this survey the author proposes an approach to resolve it. The emerging conclusion is that corporate governance is likely to develop endogenously and depend on specific characteristics of the firm and its environment.